ANALYSIS OF THE ROLES OF REGIONAL GOVERNMENT OF SAMPANG REGENCY IN CONTROLLING SANDSTONE MINING ACTIVITIES: A Case Study in Gunung Rancak Village, Robatal District, Sampang, Madura - Sushanty, Vera Rimbawani; Putra, Jejein Indramayu (YURIS: Journal of Court and Justice, 2023)
The objectives of this research are to find out, analyze, and identify the consequences of sandstone mining in Gunung Rancak Village, Robatali District on environmental damage that is crowded with visitors analyzed based on Law No. 32/2009; and to find out the role of local governments in illegal sandstone mining and negative impacts on society and obligations to create a final project paper of research on the implementation of Law No. 32/2009 regulations on sandstone mining in Gunung Rancak Village. This type of research is empirical juridical. This type is an approach that aims to find out social symptoms and problems related to existing regulations in Indonesia. Researchers used interview techniques with various parties including the Head of Sampang Regency Environmental Service, the Head of Gunung Rancak Village and the people of Gunung Rancak Village regarding sandstone mining activities in Gunung Rancak Village. The result of this research is that mining activities in Gunung Rancak Village, Robatali District cause various environmental damages, both in the abiotic and biotic categories. The impact of illegal sandstone mining activities on the community and local government has a negative impact and various provisions contained in Law No. 32/2009.